2023
DOI: 10.1186/s13595-022-01165-5
|View full text |Cite
|
Sign up to set email alerts
|

Two new methods applied to crown width additive models: a case study for three tree species in Northeastern China

Abstract: Key message The non-linear seemingly unrelated regression mixed-effects model (NSURMEM) and generalized additive model (GAM) were applied for the first time in crown width (CW) additive models of larch (Larix gmelinii Rupr.), birch (Betula platyphylla Suk.), and poplar (Populus davidiana Dode). The crown radii in four directions (CR) exhibited different growth trends and responded differently to tree size and competition variables. In the absence of calibration, GAM was more accurate than NSURM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
(161 reference statements)
0
0
0
Order By: Relevance
“…A comparison of the Korf model with the Richards and Schumacher models in the present study showed that the former displayed improved performance in predicting the SBA of B. platyphylla [68]. Within mixed forests, biological characteristics [69], interspecific effects [44], and spatial distribution pa erns [37] of different tree species affect the tree growth and development process [70]. Hence, there is a greater emphasis on selecting the model for predicting SBA that optimizes prediction accuracy and model applicability.…”
Section: Selection Of An Optimal Model For Predicting Sbamentioning
confidence: 72%
“…A comparison of the Korf model with the Richards and Schumacher models in the present study showed that the former displayed improved performance in predicting the SBA of B. platyphylla [68]. Within mixed forests, biological characteristics [69], interspecific effects [44], and spatial distribution pa erns [37] of different tree species affect the tree growth and development process [70]. Hence, there is a greater emphasis on selecting the model for predicting SBA that optimizes prediction accuracy and model applicability.…”
Section: Selection Of An Optimal Model For Predicting Sbamentioning
confidence: 72%